2008
DOI: 10.1016/j.nbd.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The release of calcium from the endoplasmic reticulum induced by amyloid-beta and prion peptides activates the mitochondrial apoptotic pathway

Abstract: In this study, we analyzed whether ER Ca2+ release, induced by amyloid-beta (Abeta) and prion (PrP) peptides activates the mitochondrial-mediated apoptotic pathway. In cortical neurons, addition of the synthetic Abeta1-40 or PrP106-126 peptides depletes ER Ca2+ content, leading to cytosolic Ca2+ overload. The Ca2+ released through ryanodine (RyR) and inositol 1,4,5-trisphosphate (IP3R) receptors was shown to be involved in the loss of mitochondrial membrane potential, Bax translocation to mitochondria and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
158
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(169 citation statements)
references
References 63 publications
9
158
0
2
Order By: Relevance
“…Moreover, we found that expression of cytochrome c and Puma were reduced, alongside with the restoration of Bcl-2/Bax and Bcl-xL/Bax ratio in the presence of biochanin A, which led to a decrease in the apoptotic rate. These data demonstrate that mitochondria are involved in the protective effect of biochanin A against Aβ [25][26][27][28][29][30][31][32][33][34][35] and that this drug attenuated Aβ 25-35 -induced PC12 cell injury and apoptosis by preventing mitochondrial dysfunction. Thus, biochanin A might raise a possibility as a potential therapeutic agent for Alzheimer's disease and other related neurodegenerative diseases.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, we found that expression of cytochrome c and Puma were reduced, alongside with the restoration of Bcl-2/Bax and Bcl-xL/Bax ratio in the presence of biochanin A, which led to a decrease in the apoptotic rate. These data demonstrate that mitochondria are involved in the protective effect of biochanin A against Aβ [25][26][27][28][29][30][31][32][33][34][35] and that this drug attenuated Aβ 25-35 -induced PC12 cell injury and apoptosis by preventing mitochondrial dysfunction. Thus, biochanin A might raise a possibility as a potential therapeutic agent for Alzheimer's disease and other related neurodegenerative diseases.…”
mentioning
confidence: 62%
“…The β-amyloid (Aβ) protein is the major component of senile plaques and has a causal role in the development and progression of AD [3]. Its peptide fragment chain Aβ [25][26][27][28][29][30][31][32][33][34][35] is the most toxic derivative, and has been universally applied in the research of AD [4]. Although the actual mechanism associated with Aβ-induced toxicity remains elusive, some studies have demonstrated evidence that oxidative stress and mitochondrial dysfunction play a role in Aβ-mediated neuronal cytotoxicity [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This scenario supports the idea that in TTR amyloidosis, same disturbance of cell/tissue function by the deposits of fibrillar material results not only from a mechanical alteration of proper oxygen and nutrient exchange, but also from more subtle biochemical and physiological modifications resulting from the interaction of deposited fibrils and/or leaked oligomers with surrounding cells. Several lines of evidence implicate amyloid oligomers as the main cytotoxic species, even though not all oligomers are cytotoxic (61,62). However, the cytotoxicity of amyloid fibrils is not surprising since it has been reported repeatedly (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…This gradient of Ca 2ϩ is tightly controlled by interactions with binding proteins and movement across the plasma membrane, in addition to transport into and out of key organelles such as the endoplasmic reticulum (ER) and mitochondria. The ER plays the role of a calcium reservoir, whereas mitochondria are a calcium sink, removing and buffering excess calcium in the cytosol (Ferreiro et al, 2008). Finely tuned changes in [Ca 2ϩ ] c modulate a variety of intracellular functions ranging from muscle contraction to secretion.…”
Section: Introductionmentioning
confidence: 99%